Does a circular convex blind spot mirror increase the driver’s field of view? - Mohd Hasnun Ariff, Hassan; Tan, F. Y.; M. A., Abdullah; N. Q., Radzuan; K. A., Abu Kassim (Society of Automotive Engineers Malaysia, 2020)
Many road traffic accidents occur in Malaysia every year. Road fatalities has been one of the main causes of death in Malaysia. More than half of these fatalities were among motorcyclists. An accident between a passenger car and a motorcycle might be caused by the blind spot of the car driver, in which the driver was unable to notice an incoming motorcycle from behind or the side. Blind spot monitoring system has been developed using recent technology. However, this active blind spot monitoring system is expensive and only available in luxury cars. Another type of blind spot monitoring is known as passive blind spot monitoring by means of a convex mirror. Many convex blind mirrors are being sold nationwide that come in various shapes. Nonetheless, the effectiveness of this convex mirror has never been quantified. This study aims to experimentally quantify the effectiveness of this mirror by using a spotlight, projecting a direct light to the side mirror. A circular convex mirror was placed at four different locations, one at a time. It is hypothesised that the reflection of the light on a flat, white wall indicates the driver’s field of view. The area of the reflection was calculated using image processing, and the values of all five cases were compared. It was found that the circular convex mirror increases the field of view by up to 211 %. The position of the convex mirror plays an important role to ensure a maximum field of view is achieved. This paper has demonstrated that the usage of a circular convex mirror does increase the driver’s field of view.